Thrombosis of the Princeps Pollicis Artery of the Thumb - Case Report of an Unusual Disease - Vieira, Maria Julia Nicolau; Curvelo Rosado, Giulia Andreia; Conti Tarifa, Lara; Duarte de Almeida, Rafael; Duarte, Márcio Luís; Duarte, Élcio Roberto (Prague medical report, 2025)
In the clinical evaluation of upper extremity embolism cases, the anamnesis should focus on identifying potential triggering risk factors. The physical examination may reveal sensory deficits, aiding in the determination of ischemia stages. Imaging diagnosis is crucial, with computed tomography (CT) angiography being the preferred examination due to its ability to provide detailed information about arterial anatomy across multiple planes and clear visualization of adjacent structures. Compared to magnetic resonance imaging angiography, CT angiography offers faster results with minimal distortion, despite the exposure to radiation and contrast use. Doppler ultrasonography is another valuable tool in suspected arterial thromboembolism cases, particularly in emergency settings. It offers advantages over CT angiography as it is non-invasive, cost-effective, and does not involve radiation or contrast administration. We present the case of a 68-year-old man who reported a nodule in the medial region of his right thumb for three months. Initially, he experienced significant local pain and limited movement, which gradually improved over time with the use of analgesic medication. Ultrasonography revealed thrombosis in the princeps pollicis artery, and the patient commenced treatment with acetylsalicylic acid. After four months, the patient reported a marked reduction in the nodule size along with pain improvement.
Keywords: Thumb; Aspirin; Princeps pollicis artery; trombóza; Ultrasonography, Doppler; Aged; Ultrasonography; Humans; Doppler; mužské pohlaví; senioři; lidé; palec ruky; CT angiografie; Male; Thrombosis; ultrasonografie dopplerovská; Computed Tomography Angiography